Two Faces of Love in A Paixao Medida, by Carlos Drummond de Andrade - Borsato, Fabiane Renata [UNESP]; Tavela, Lysllaynne Pryscylla [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2019)
This paper analyzes two poems from the work A Paixao Medida (1980) aiming to comprehend the two faces of love underlying Carlos Drummond de Andrade's poetics, being the first one the marketable love in the poem A festa do mangue, and the second one being the epiphanic love, presented in the poem Nascer de novo. In order to do it, the modes of instauration of the voices in the poems will be described and analyzed they are grounded either in the first person's objectivity or in its intense subjectivity; the gradations and rhythmic regularity; the relation between the identity and the epiphany; love as a friendly conception of things and alterity; the relation between locus adversus and locus amoenus; the presence of Drummond's irony; the empathetic gaze of the poetic persona towards the existence conditions on the mangrove; the spatial mobility of the mangrove's clients as a counterpoint of the prostitutes' isolation and maintenance of the social and economic exclusion. The subjects of both of these poems, facing the economic, political and social adversities, seek alternatives of existence and surviving in a disarranged world. It is aimed to highlight that the transitory love of the mangrove and the love-poetry-epiphany are two of Drummond's forms of love amid the tough mythology of the modern cities.
Keywords: Carlos Drummond de Andrade; A Paixao Medida; loving lyric